Thermographic Evaluation of the Duration of Skin Cooling After Cryotherapy in Dogs Following Tibial Plateau Leveling Osteotomy Surgery - Woo, Sang Chul; Lee, Jack; Millis, Darryl L.; Drum, Marti G. (Frontiers in Veterinary Science, 2022)
Objective To evaluate the duration of cooling after cryotherapy on the skin over stifle joints in dogs after tibial plateau leveling osteotomy (TPLO) surgery using thermography. Materials and Methods Seventeen client-owned dogs of various breeds were enrolled in the study. Dogs underwent TPLO surgeries, and on the next day, thermal imaging was performed on the operated stifle prior to cryotherapy for baseline. Orthogonal views were repeated at 30-minute intervals until the skin over the stifle had thermally equilibrated. An ice pack was applied for 20 minutes on the medial and lateral aspects of the stifle. Each stifle was then re-imaged every 15 minutes for the first 60 minutes then every 30 minutes subsequently until the temperature was within 1°C of the pre-cryotherapy temperature. Results Mean skin temperature of the medial view showed no significance difference compared to baseline value at 45 minutes after cryotherapy was discontinued and after 60 minutes for the lateral and cranial views. Mean skin temperature was overall higher in the medial view compared to the lateral and cranial during the rewarming period (except immediately after cold application). Mean skin temperatures of all views combined showed a significant decrease in temperature during cryotherapy application, with a slow increase until a plateau was reached after 45 minutes of rewarming. Conclusions and Clinical Relevance Dogs undergoing TPLO for cranial cruciate ligament injury showed quicker rewarming period of superficial tissues compared to previous studies. Cryotherapy is a beneficial modality to reduce superficial tissue temperature in dogs undergoing TPLO, acknowledging that these dogs may require more frequent cryotherapy post-operatively due to more rapid rewarming time compared to dogs without surgery.